A formação da classe operária na era da empregabilidade : as experiências do Colégio Metalúrgico-RJ (a formação profissional em tempos de neoliberalismo, nova LDB e reestruturação produtiva) - Vilarinho Junior, Paulo Bretas (2004)
The objective of this Dissertation is to analyze current functioning of the Colégio Metalúrgico Elpídio Evaristo dos Santos (CMEES). The used methodological procedures had articulated three simultaneous movements that make possible a bigger apprehension of the studied totality: A - Revision of literature aiming at to structuralize a base of analysis of the current reality, in its conjunctural and structural dimensions, approaching the following subjects: Globalization e neoliberalism; Responsability of the World Bank in the definition of the educational politics in Brazil; New LDB and the Professional Education and Decree 2.208/97; The third industrial revolution and the productive and managemental reorganization; The challenges of the Syndical Movement in the neoliberalist years; The historical conditions of the changes of route of the Syndical Movement in the decade of 1990; The reduction of the industry in Rio de Janeiro; The new direction of the Union of the Metallurgist of Rio de Janeiro; Conceptualization of the Colégio Metalúrgico Elpídio Evaristo dos Santos: pedago gical description, proposal, current situation. B - Survey of primary sources concerning the subject in the quantity of the Union: program of elect plates, resolutions of the congresses of the category, periodicals and bulletins. C - Accomplishment of interviews half- structuralized with the Technical-Pedagogical Team, employees, professors of the CMEES and directors of the union of the Metallurgist of period 1996-2002, in order to get more given on the politics implemented for the Directions in the period and survey through questionnaires, with students who already exert functions techniques in daily practical its of work, aiming at to know its perception concerning the theory-practical relation of the contents given in the CMEES. I conclude quite to the contrary that the politics implemented for the directions of the Union in period 1996-2002 had not contributed for the emptiness of the CMEES. The interviews had been unanimous in disclosing that, where they weigh the deficiencies in the process, without the support given until here for the Union, the CMEES probably already would have been closed. The current crisis is caused by the combination of the some conditions studied to the long one of this Dissertation.